Pheochromocytoma in a child without hypertension: A contribution to the “rule of 10s” - Prasanta Kumar Tripathy; Kaumudee Pattnaik; Manjushree Nayak; Hiranya Kishor Mohanty (Indian Journal of Medical and Paediatric Oncology)
Pheochromocytoma (PCC) is a neuroendocrine tumor originating from chromaffin tissue in adrenal medulla. Its diagnosis and treatment are well defined in adults, but experience in children is limited. Children constitute only 10% of reported cases, the average age at presentation being 11 years. The most common presentation is sustained hypertension, which is absent in only 10% of children. We managed a 14-month-old female child with PCC, but she was not hypertensive. We report two unusual features, in this case, an extremely young age at presentation and a childhood case of nonhypertensive PCC contributing for “rule of 10s.”